The Possibility of Including Medical Ethics Courses in the Clinical Training of Medicine Students: Academic Members Viewpoints - Mohammad Reza Yosefi; Mohammad Reza Ghanbari; Mohammad Ali Mohagheghi; Seyed Hasan Emami Razavi (Strides in Development of Medical Education, 2012)
Background & Objective: In spite of supreme goals of Medical Ethics Education it seems that the current Medical curriculum does not have the sufficient capability of influencing attitude and behavior The main purpose of this study was to evaluate the necessity and possibility of including medical ethics courses in the clinical training period Methods: This qualitative study was performed with a case study approach Subjects were the academic members of faculty of Medicine in Tehran University of Medical Sciences In depth interview and focused group discussion were used fore data collection Data analysis was performed using text analysis analytical method Retrieved conception codes were classified as six main conceptions and related subconceptions Results : Data analysis for the necessity part resulted in the necessity of including Medical Ethics in clinical training applied familiarity with medical ethics issues simultaneous education and clinical application of medical ethics issues beneficial effect of including medical ethics as a course in the clinical period longterm experience of ethics issues and teachers behaviors in clinical setting and nontheoretical aspect of some ethics issues Main issues in the challenges part were insufficient familiarity of teachers with ethics subjects and ways to transfer them administrative problems of program implementation problems of educational system the impact of cultural shortage in programming and shortage of skilled lecturers in medical ethics In relation to the possibility main issues were the possibility of including medical ethics in the clinical period training teachers for ethics subjects and presenting them to the students programming and preparing course contents in accordance with the societys culture tradition and religion using experienced and skilled teachers and avoiding direct use of programs designed in foreign countries Conclusion: Including medical ethics courses in the clinical training period in order to decrease professional problems seems to be necessary Moreover considering the potentials of our society it is possible to consider medical ethics courses in our Medical Education